NASIONALISME ETNIK DI KALIMANTAN BARAT - Kristianus Kristianus (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
Nowadays ethnical celebration triggered by the uncontrollable identity politics,is happening in Indonesia. In West Kalimantan, for instance, a struggle for theidentity politics has succeeded in forming new governments in district levels.The new district governments are always based on the dominant ethnic groupsin the area. The political impact of the identity politics can whip up the ethnicalspirit by giving hegemony to ethnic monitory in the area. This paper argues thatthis phenomenon could become ethnic nationalism. Theoretically, identitypolitics is a struggle of a group or marginal people (periphery) politically,socially as well as culturally and economically. Various ethnic con?icts inWest Kalimantan relate to the identity politics and the resistance towardsthe hegemony of the ruling ethnic elite. The paper concludes that the ethniccon?icts in West Kalimantan are the forms of effort of an ethnic group toshow their existence. These people have been threatened, or for a longtime they have been marginalized systematically, so that their spirit to fghtagainst hegemony rise. Identity politics appearing in the forms of culturalinstitution such as ethnic customary council could be explained as the ethnicsystematic efforts to strengthen their identity, which eventually could becomea prospective ethnic nationalism.Key words : Politics, identity, con?icts, nationalism, ethnic, hegemony.